MMP2 and MMP10 Polymorphisms Are Related to Steroid-Induced Osteonecrosis of the Femoral Head among Chinese Han Population. (5th May 2019) - Tian, Ye; An, Feimeng; Wang, Jiaqi; Liu, Chang; Wu, Huiqiang; Cao, Yuju; Wang, Jianzhong; Wang, Guoqiang
Abstract : Background . Steroid-induced osteonecrosis of the femoral head is a relatively serious condition which seriously reduces patient quality of life. However, the pathogenesis of steroid-induced ONFH is still unclear. In recent years, more scholars have found that the pathogenesis of steroid-induced ONFH is related to susceptibility factors such as MMPs / TIMPs system. The main purpose of this study is to investigate the correlation between MMP2 and MMP10 gene polymorphisms and steroid-induced ONFH in Chinese Han population. Methods . Six SNPs in MMP2 and two SNPs in MMP10 were genotyped using Agena MassARRAY RS1000 system from 286 patients of steroid-induced ONFH and in 309 healthy controls. The association between MMP2 and MMP10 polymorphisms and steroid-induced ONFH risk were estimated by the Chi-squared test, genetic model analysis, haplotype analysis, and stratification analysis. The relative risk was estimated by odd ratios (ORs) and 95% confidence intervals (CIs). Result . We found that the minor TG allele of rs470154 in MMP10 was associated with an increased risk of steroid-induced ONFH (OR = 1.45, 95% CI, 1.03 – 2.05, p = 0.032). In the genetic model analysis, we found that rs2241146 in MMP2 gene and rs470154 in MMP10 gene showed a statistically significant association with increased risk of steroid-induced ONFH. The six SNPs (rs470154, rs243866, rs243864, rs865094, rs11646643, and rs2241146) showed a statistically significant association with different clinical phenotypes. Conclusion . Our results verify that genetic polymorphisms of MMP2 and MMP10 contribute to steroid-induced ONFH susceptibility in the population of Chinese Han population, and our study provides new insights into the role that MMP2 and MMP10 plays in the mechanism of ONFH.